NILAI-NILAI KEBUDAYAAN DALAM MATAN KEYAKINAN DAN CITA-CITA HIDUP MUHAMMADIYAH - Sarbini, Sarbini (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2016)
Muhammadiyah, founded by Ahmad Dahlan is a cultural forms, which reflected a critical attitude Ahmad Dahlan in 1912. This can be seen from a variety of social activities, modern school education, health care, compensation for orphans and the elderly as well as the issuance of the press, as well as in Islamic sermon. The forms of the empirical culture stored in Ahmad Dahlan thought within the framework of realization the spirit of the Islamic functional values.